Coexisting Parallelogram Method to Handle Jump Point on Hough Transform-based Clock Skew - Putra Sastra, Nyoman (Array, 2021)
In this paper, we improve the robustness of the Hough transform-based clock skew measurement on the occurrence of a jump point. The current Hough transform-based skew method uses angle (θ), thickness (ω), and region (β), to create a parallelogram that covers the densest part of an offset-set. However, the assumption that all offsets are considered to line up roughly in only one direction restricts the ability of the current method when handling an offset-set in which its densest part is located separately, the jump point condition. By acquiring the parallelogram from coexisting angle-region tuples at the beginning and the ending parts of the offset-set, we completed the ability of the Hough transform-based method to handle the jump point. When handling the jump point problem, the proposed coexisting parallelogram method could reach 0.35 ppm accuracy compared with tens ppm by the current methods.